A Comperative Study on Wiener Filter and Wavelet Transform for Energy Management Systems on Hybrid Unmanned Aerial Vehicles - Bayram, Serhat; Boynuegri, Ali Rifat (IEEE, 2020)
Unmanned Aerial Vehicles (UAV) with electric power engines are popular research topic. Especially the hybrid powered ones with alternative energy sources are coming into prominence. However the characteristic behavior of alternative energy sources causes a need on complex Energy Management System (EMS). This paper proposes an EMS for fuel cell and ultracapacitor hybrid fixed wing UAV. So, the Wavelet transform and Wiener filter are used as two different techniques to create the EMS. In this study, the results of the Wiener Filter and Wavelet transform techniques were compared using experimental flight data. The system is modeled with MATLAB/Simulink (R), the advantages and disadvantages of these methods are compared. Only, the fuel cell and ultracapacitor are used in this system for a fair comparison.
Keywords: UAV; energy storage systems; energy management; power demand; fuel cell; ultracapacitor; hybrid power system; wavelet transform; wiener filter; POWER; Energy & Fuels; Engineering